The Boy with a Broken Heart - Durjoy Datta (Penguin, 2017)
It's been two years since Raghu left his first love, Brahmi, on the edge of the roof one fateful night. He couldn't save her; he couldn't be with her. Having lost everything, Raghu now wants to stay hidden from the world. However, the annoyingly persistent Advaita finds his elusiveness very attractive. And the more he ignores her, the more she's drawn to him till she bulldozes her way into an unlikely friendship. What attracts at first, begins to grate. Advaita can't help but want to know what Raghu has left behind, what he's hiding, and who broke his heart. She wants to love him back to life, but for that she needs to know what wrecked him in the first place. After all, the antidote to heartache is love